Social motives in a patient with bilateral selective amygdala lesions: shift in prosocial motivation but not in social value orientation - Doppelhofer, Lisa M.; Hurlemann, René; Bach, Dominik; Korn, Christoph W. (Neuropsychologia, 2021)
Humans hold social motives that are expressed in social preferences and influence how they evaluate and share payoffs. Established models in psychology and economics quantify social preferences such as general social value orientation, which captures people's tendency to be prosocial or individualistic. Prosocials further differ by how much they maximize joint gains or minimize inequality. Functional neuroimaging studies have linked increased amygdala activity in prosocials to payoff inequality between self and other. However, it is unclear whether amygdala lesions alter social motives. We used two tasks to test a patient with selective bilateral amygdala lesions and three healthy samples (a priori matched control sample N = 20, online sample N = 603, student sample N = 40), which allowed us to assess and model social motives across a relatively large number of participants. In a social value orientation task, the patient was categorized as prosocial and her social value orientation score did not differ from healthy participants. Importantly, the patient differed in prosocial motivation by maximizing joint gains rather than minimizing payoff inequality. In a joint payoff evaluation task, Bayesian model comparisons revealed that participants' evaluations were best described by models, which link participants' evaluations to the payoff magnitude and to inequality. Overall, amygdala lesions did not seem to alter general social value orientation but shifted prosocial motivation toward maximizing joint gains.
Gesehen am 07.02.2022